Persistent and obscene inequality: A post-apartheid policy choice - Mohamed, Seeraj (New Agenda: SA Journal of Social and Economic Policy, 2024)
How is one to understand the poor economic performance of the South African economy since the end of apartheid SEERAJ MOHAMED argues that the post-apartheid government chose to adopt neoliberal economic policies rather than taking on a developmental state role. These policies opened the way for the large dominant corporations to pursue high short-term returns through misallocating capital from productive sectors towards speculation and “lazy” rent-seeking activities. In the process they denuded, deindustrialised and financialised the economy. Still today, the South African government (supported by elites of large corporations) ignores the lessons of history and pursues damaging neoliberal economic policies that impose an unprecedented degree of suffering on the majority of South Africans.